POETIC RESPONSIVE OF NARRATIVE POETRY FROM D. ZAWAWI IMRON DURING THE PANDEMIC OF COVID-19 - Susi Darihastining; Hetty Purnamasari; Daroe Iswatiningsih; Heny Sulistyowati; Titik Indarti (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
An ethno poetics of narrative poem from D. Zawawi Imron attempts to stimulate social sensitivity during the current pandemic of Covid-19. This research aims at analyzing a narrative poem of D. Zawawi Imron as a cultural response during the current pandemic of Covid-19. This research employed an ethno poetics framework to analyze the narrative poem. In addition, it took a linguistics perspective suggested by Jacobson. This paper further discussed (1) how do the repeating words form that poetically responding from a narrative poem of D Zawawi Imron during the current pandemic of Covid-19? And how the meaning of the repeating words that poetically responding from the narrative poem of D Zawawi Imron during the current pandemic of Covid-19? The observation results indicate that the narrative poem of D Zawawi Imron entitled “Tiarap” (Prone in English) contains the poetic and cultural response. The analysis was conducted by using descriptive qualitative procedures. The approach used was an ethno poetics approach. The data source was an audio-visual document of D. Zawawi Imron’s poem entitled “Tiarap” (Prone in English) which was recently published during the pandemic of Covid-19. The data of this research was in the form of (1) the repeating words that are poetically responding to the narrative poem of D. Zawawi Imron during the current pandemic of Covid-19 and (2) the meaning of the repeating words that poetically responding to the narrative poem of D. Zawawi Imron during the current pandemic of Covid-19. The data were further analyzed by using the poetics analysis model. The results show that there are repeating words of alliteration, assonance, adjective repeating words, reduplication, and reduplication of the durative aspect. In addition, it obtained a direct and indirect meaning.